Brain Metastases From Differentiated Thyroid Carcinoma: A Retrospective Study of 22 Patients - Wu, Tong; Jiao, Zan; Li, Yixuan; Peng, Jin; Yao, Fan; Chen, Weichao; Yang, Ankui (Frontiers in Endocrinology, 2021)
Background Brain metastasis from differentiated thyroid cancer has followed a similar increasing trend to that of thyroid cancer in recent years. However, the characteristics and treatments for brain metastases are unclear. The aim of this study was to understand this disease by analyzing patients with brain metastases from differentiated thyroid cancer (DTC). Methods Between 2000 and 2020, the database of the Sun Yat-sen University Cancer Center was searched for differentiated thyroid cancer patients. We identified a cohort of 22 patients with brain metastases. The characteristics of the patients, histological features, treatments, and time of death were reviewed. The overall survival (OS) rate was calculated using the Kaplan Meier method. Survival curves of different subgroups were compared according to baseline characteristics and treatments received. Results A total of 22 (1.09%) out of 2013 DTC patients in the Sun Yat-sen University Cancer Center database were identified as having brain metastases. The overall median survival time was 17.5 months (range from 1–60 months) after diagnosis of brain metastasis. Performance statue (PS), tumor site, and neurosurgery impacted survival, according to Kaplan-Meier analysis. Prognosis of skull metastasis was superior to that of intracranial types. Neurosurgery was the only type of treatment that had an impact on patient OS. Conclusions Brain metastasis from differentiated thyroid cancer has a poor prognosis. However, it can be improved by comprehensive treatment. PS of the patients can greatly affect survival. Skull metastases have improved prognosis over intracranial types. Radioiodine therapy (RAIT) appears to effectively improve the prognosis of patients with skull metastases from DTC.